Manajemen Pembelajaran Berbasis Budaya Lokal Sasak Begibung Guna Membentuk Karakter Profil Pelajar Pancasila di TK Negeri Pembina Ampenan - Zalza Aprilian Syahbi; Ika Rachmayani; Baiq Nilawati Astini; Nurhasanah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Learning management is a systematic process aimed at organizing all instructional activities to achieve educational objectives effectively and efficiently. This study aims to identify and analyze the implementation of learning management that integrates the local Sasak cultural tradition of begibung in shaping the character of the Pancasila Student Profile at TK Negeri Pembina Ampenan. The begibung tradition, a communal dining practice of the Sasak community, is considered capable of fostering gratitude to God Almighty, independence, mutual cooperation, and global diversity awareness among young children. This research employed a descriptive qualitative method using observation, in-depth interviews with teachers and the principal, and documentation of learning activities. The findings indicate that culture-based learning management through the begibung activity has been effective in developing the character values of the Pancasila Student Profile. The study recommends the consistent implementation of this local culture-based approach to instill positive character values from an early age.